Trajectories of child cognitive development during ages 0-3 in rural Western China: prevalence, risk factors and links to preschool-age cognition - Lei Wang; Yifei Chen; Sean Sylvia; Sarah-Eve Dill; Scott Rozelle (BMC, 2021)
Abstract Background Cognitive development after age three tends to be stable and can therefore predict cognitive skills in later childhood. However, there is evidence that cognitive development is less stable before age three. In rural China, research has found large shares of children under age three are developmentally delayed, yet little is known about the trajectories of cognitive development between 0 and 3 years of age or how developmental trajectories predict later cognitive skills. This study seeks to describe the trajectories of child cognitive development between the ages of 0-3 years and examine how different trajectories predict cognitive development at preschool age. Methods We collected three waves of longitudinal panel data from 1245 children in rural Western China. Child cognitive development was measured by the Bayley Scales of Infant Development when the child was 6-12 months and 22-30 months, and by the Wechsler Preschool and Primary Scale of Intelligence-Fourth Edition when the child was 49-65 months. We used the two measures of cognitive development before age three to determine the trajectories of child cognitive development. Results Of the children, 39% were never cognitively delayed; 13% were persistently delayed; 7% experienced improving cognitive development; and 41% experienced deteriorating development before age 3. Compared to children who had never experienced cognitive delay, children with persistent cognitive delay and those with deteriorating development before age 3 had significantly lower cognitive scores at preschool age. Children with improving development before age 3 showed similar levels of cognition at preschool age as children who had never experienced cognitive delay. Conclusions Large shares of children under age 3 in rural Western China show deteriorating cognitive development from infancy to toddlerhood, which predict lower levels of cognition at preschool age. Policymakers should invest in improving cognitive development before age 3 to prevent long-term poor cognition among China's rural children.